Ocho líneas de investigación en salud mental emergentes con la pandemia (2021)
COVID-19 is not only, in itself, an object of investigation. It also brought to the table topics that have been little explored and even little thought about, especially in mental health. His arrival reordered and modified the science agenda worldwide and opened the door to analysis from the social sciences as well. For this reason, studies have emerged that cover topics related to behavioral sciences, new ways of establishing interpersonal relationships and impacts on cognitive and professional development, among others. In addition, they take into account segmentations such as, for example, population groups, countries and gender.